SPIRA: Building an Intelligent System for Respiratory Insufficiency Detection - Ferreira, Renato Cordeiro; Gomes, Dayanne; Tamae, Vitor; Wernke, Francisco; Goldman, Alfredo (Anais do Workshop Brasileiro de Engenharia de Software Inteligente (ISE), 2022)
Respiratory insufficiency is a medic symptom in which a person gets a reduced amount of oxygen in the blood. This paper reports the experience of building SPIRA: an intelligent system for detecting respiratory insufficiency from voice. It compiles challenges faced in two succeeding implementations of the same architecture, summarizing lessons learned on data collection, training, and inference for future projects in similar systems.